A mobility model for opportunistic networks in commercial areas. (2016) - Yang, Wanchun; Peng, Shiyao
In this paper, we propose a mobility model for opportunistic networks in a commercial area (MMCA). The commercial area is divided into two parts: internal and external areas. We modified the traditional susceptible-infected-removed (SIR) model for predicting the performance of the message forwarding in MMCA. Using the opportunistic networks environment (ONE) simulation platform, we validated this modified SIR by comparing the theoretical results and modelled data from ONE. We further analyse the performances of MMCA with the number of nodes, walking speeds, communication ranges and the size of areas.